2006
DOI: 10.1161/circulationaha.105.602094
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII Deficiency Causes Cardiac Rupture, Impairs Wound Healing, and Aggravates Cardiac Remodeling in Mice With Myocardial Infarction

Abstract: Background-Identification of key molecular players in myocardial healing could lead to improved therapies, reduction of scar formation, and heart failure after myocardial infarction (MI). We hypothesized that clotting factor XIII (FXIII), a transglutaminase involved in wound healing, may play an important role in MI given prior clinical and mouse model data. Methods and Results-To determine whether a truly causative relationship existed between FXIII activity and myocardial healing, we prospectively studied my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
140
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 28 publications
10
140
0
Order By: Relevance
“…Cardiac rupture of factor XIII deficient mice (FXIII −/− and FXIII −/+ ) occurred between 3 and 5 days after MI, consistent with clinical observations of this complication (180). Cardiac ruptures were likely due to an imbalance in ECM turnover, since MMP-9 expression was 7-fold higher and collagen-1 production was 53% lower in FXIII −/− mice (180). Replenishing Factor XIII levels in FXIII −/− mice reduced cardiac rupture and death rates to those observed in wild type mice.…”
Section: Effects Of Factor XIII On Myocardial Healing After Misupporting
confidence: 82%
See 3 more Smart Citations
“…Cardiac rupture of factor XIII deficient mice (FXIII −/− and FXIII −/+ ) occurred between 3 and 5 days after MI, consistent with clinical observations of this complication (180). Cardiac ruptures were likely due to an imbalance in ECM turnover, since MMP-9 expression was 7-fold higher and collagen-1 production was 53% lower in FXIII −/− mice (180). Replenishing Factor XIII levels in FXIII −/− mice reduced cardiac rupture and death rates to those observed in wild type mice.…”
Section: Effects Of Factor XIII On Myocardial Healing After Misupporting
confidence: 82%
“…Mice with even relatively mild deficiency of factor XIII (70% activity in FXIII+/− mice) displayed this phenotype. Cardiac rupture of factor XIII deficient mice (FXIII −/− and FXIII −/+ ) occurred between 3 and 5 days after MI, consistent with clinical observations of this complication (180). Cardiac ruptures were likely due to an imbalance in ECM turnover, since MMP-9 expression was 7-fold higher and collagen-1 production was 53% lower in FXIII −/− mice (180).…”
Section: Effects Of Factor XIII On Myocardial Healing After Misupporting
confidence: 67%
See 2 more Smart Citations
“…Earlier studies showed deleterious consequences (including a worsening of ventricular remodeling) following inhibition of fibrotic healing or the inflammatory response after infarction by means of corticosteroids. 29,30 Recent research on genetically modified mice has also demonstrated the adverse consequences of impaired fibrotic healing after MI leading to aggravated ventricular rupture and remodeling, 31,32 although the suppression of excessive matrix deposition is believed to be beneficial in the context of stem cell based therapies. Our findings showed that fibrotic healing post-infarction can be therapeutically remodeled by relaxin leading to a reduced density of fibrotic tissue across infarcted, non-infarcted, and border zones.…”
Section: Discussionmentioning
confidence: 99%